Avian Influenza A Virus Infects Swine Airway Epithelial Cells without Prior Adaptation - Dai-Lun Shin; Wei Yang; Ju-Yi Peng; Bevan Sawatsky; Veronika von von Messling; Georg Herrler; Nai-Huei Wu (Viruses, 2020)
Pigs play an important role in the interspecies transmission of influenza A viruses (IAV). The porcine airway epithelium contains binding sites for both swine/human IAV (α2,6-linked sialic acids) and avian IAV (α2,3-linked sialic acids) and therefore is suited for adaptation of viruses from other species as suggested by the “mixing vessel theory”. Here, we applied well-differentiated swine airway epithelial cells to find out whether efficient infection by avian IAV requires prior adaption. Furthermore, we analyzed the influence of the sialic acid-binding activity and the virus-induced detrimental effects. Surprisingly, an avian IAV H1N1 strain circulating in European poultry and waterfowl shows increased and prolonged viral replication without inducing a strong innate immune response. This virus could infect the lower respiratory tract in our precision cut-lung slice model. Pretreating the cells with poly (I:C) and/or JAK/STAT pathway inhibitors revealed that the interferon-stimulated innate immune response influences the replication of avian IAV in swine airway epitheliums but not that of swine IAV. Further studies indicated that in the infection by IAVs, the binding affinity of sialic acid is not the sole factor affecting the virus infectivity for swine or human airway epithelial cells, whereas it may be crucial in well-differentiated ferret tracheal epithelial cells. Taken together, our results suggest that the role of pigs being the vessel of interspecies transmission should be reconsidered, and the potential of avian H1N1 viruses to infect mammals needs to be characterized in more detail.